2014
DOI: 10.1007/s00464-014-3622-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the pathological features of the mesorectum before the laparoscopic approach to rectal cancer

Abstract: Pelvic anatomy and tumour features play a role in the difficulty of the laparoscopic approach to total mesorectal excision in rectal cancer. The aim of the study was to analyse whether these characteristics also influence the quality of the surgical specimen. We performed a prospective study in consecutive patients with rectal cancer located less than 12 cm from the anal verge who underwent laparoscopic surgery between January 2010 and July 2013. Exclusion criteria were T1 and T4 tumours, abdominoperineal rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Pelvimeter is no longer just obstetric assessment tool, but widely used in the evaluation of rectal cancer before surgery. A lot of researches have proved that there is a link between the pelvic measurement parameters and operation time, intraoperative bleeding volume, difficulty of operation, ring margin positive rate, surgical specimen integrity, even postoperative anastomotic fistula of rectal cancer surgery [ 11 13 , 20 ]. In this study, two methods of laparoscopic surgery was used, one was laparoscopic anterior resection in which the part of the rectum containing the tumor was removed and the colon was then attached to the remaining part of the rectum so that bowels can be empty in the usual way, second was MILES which involved removal of the anus and the tissues surrounding it, including the sphincter muscle and a permanent colostomy was done since the anus was removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvimeter is no longer just obstetric assessment tool, but widely used in the evaluation of rectal cancer before surgery. A lot of researches have proved that there is a link between the pelvic measurement parameters and operation time, intraoperative bleeding volume, difficulty of operation, ring margin positive rate, surgical specimen integrity, even postoperative anastomotic fistula of rectal cancer surgery [ 11 13 , 20 ]. In this study, two methods of laparoscopic surgery was used, one was laparoscopic anterior resection in which the part of the rectum containing the tumor was removed and the colon was then attached to the remaining part of the rectum so that bowels can be empty in the usual way, second was MILES which involved removal of the anus and the tissues surrounding it, including the sphincter muscle and a permanent colostomy was done since the anus was removed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the deep and narrow pelvis is positively associated with operation time and bleeding volume [ 11 , 12 ]. Moreover, the sacrum angle and pelvic measurements were associated with making preoperative decision in TME surgery [ 13 ] . Is there any relationship between the choice of laparoscopic surgery for rectal cancer and pelvic measurements?…”
Section: Introductionmentioning
confidence: 99%
“…In advanced stages, the involvement of the perirectal fascia may be of prognostic importance. To date, it was assumed that its involvement could only be assessed with MRI, but newer studies have shown that EUS can also detect infiltration of the perirectal fascia [ 136 ].…”
Section: Diagnostic Endoscopic Ultrasoundmentioning
confidence: 99%
“…This indicator of quality of surgery also has prognostic value, and is therefore a mandatory discussion point in multidisciplinary team meetings (MDTs). For rectal cancer, this has become a surrogate marker in surgical trials that facilitate the introduction of new techniques . For colon cancer, a similar system has been developed (Table ) which needs prospective validation …”
Section: Macroscopic Considerationsmentioning
confidence: 99%
“…For rectal cancer, this has become a surrogate marker in surgical trials that facilitate the introduction of new techniques. 7,8 For colon cancer, a similar system has been developed ( Table 1) which needs prospective validation. [9][10][11]…”
Section: O M P L E T E N E S S O F R E S E C T I O Nmentioning
confidence: 99%